Measuring Customers' Perception At MOHME Department Of Health, With National Productivity And Organizational Excellence Award Of Iran - Seyed Davood Nasrollapour Shirvani; Mohammad Esmaeil Motlagh; Mohammad Shariati; Pari Haji Seiyed Azizi; Azin Nahvijou (Tehran University of Medical Sciences, 2016)
Background and Aim: Today, customer perception assessment as a way to measure satisfaction and expectations has an important role in improving the quality of services and organizational excellence. This study aims to measure customers' perception at the Health Deputy of Iran's Ministry of Health and Medical Education (MOHME). Materials and Methods: This cross-sectional study was performed in 2012-2013. The population comprised the health deputies of medical universities, among which 13 of the universities were randomly selected. As the main customers of MOHME health deputy, these universities' managers and experts were asked questions like a census. The data collection device was the national award standard questionnaire consisting of 2 sections and 26 questions. The data were analyzed by SPSS 18 with level. Results: Of the 267 managers and experts, 147 (56.1%) were male. Many of them (57.3%) had a bachelorchr('39')s degree. Most of them (91.6%) were employed in technical units. The average perceived level of managers and experts regarding their reputation and image was 3.3±0.7, production and service 3.1±0.7, support while and after providing services 3.0±0.7, and loyalty and honesty 3.3±0.8 out of a maximum 5 points, respectively. There was no significant relationship between administrators and experts' perception level on the one hand, and individual and organizational factors on the other (P>0.05). Conclusion: The study showed that customers' perception of indices related to the quality of relationships, services and measures was at a moderate level. Therefore, it is recommended that the department of health should design and implement an appropriate intervention program for organizational excellence.